Konsep Hidup Pantun Sasak Sebagai Refleksi Nilai- Nilai Budaya Lokal: Analisis Pemanfaatan Sebagai Bahan Ajar Sekolah - Agus Jayadi; Padlurrahman Padlurrahman; Badarudin Badarudin (Educatio, 2025)
This study examines the potential integration of Sasak pantun as character education material at SMPN Satu Atap 1 Terara, East Lombok. Sasak pantun, a form of traditional oral literature, historically functioned as a medium for conveying moral messages and social values in Sasak society. Over time, the use of pantun has significantly declined, especially among the younger generation. As an educational institution situated within a culturally rooted community, the school holds strategic potential to revive the educational function of pantun through formal instruction. This research is grounded in the theories of character education based on local wisdom, cultural transmission, and contextual learning approaches. These frameworks are employed to explore the relationship between the cultural values embedded in Sasak pantun and the goals of character development in students. The study adopts a qualitative approach using the Miles and Huberman interactive analysis model, comprising data reduction, data display, and conclusion drawing. Triangulation of sources and techniques was applied to ensure data validity. Data were collected through in-depth interviews with teachers, school administrators, and local cultural figures, as well as classroom observations and curriculum document analysis. The findings reveal that Sasak pantun contains values of religiosity, mutual cooperation, humility, and respect—core elements of character education. However, its integration is hindered by the absence of curricular policy, limited teaching resources, and insufficient teacher training. The study concludes that Sasak pantun plays a vital role as both a medium for character education and cultural preservation, and should be prioritized within school-based learning.